Why Does Snow White Crave Blood? Pop Culture Vampiric Variations on the Grimms’ Fairy Tale - Kostecka, Weronika; Skowera, Maciej (Porównania, 2023)
As a meme—a cultural replicator—the fairy tale about Snow White has high viral potential in Jack Zipes’s understanding. Research conducted on this cultural text has revealed the presence of its several hundred versions on several continents, with the best-known literary variant being the Grimms’ one. In this paper, we focus on the comparative analysis of the vampiric incarnations of Snow White in three literary works: the short stories Snow, Glass, Apples by Neil Gaiman (1994) and Red as Blood by Tanith Lee (1983), and Rashelle Workman’s novel Blood and Snow (2013). They show clear affinities with the Grimms’ variant: whether at the implicit level, using plot, aesthetic, and components canonized by this version, or at the explicit level, through direct paratextual and metafictional clues. Thus, we make an attempt to add to the state of research on popular culture images of the vampire, and at the same time to join the current of Grimmological studies developing in our country.